Insomnia disorder update: the benefits of screening and treatment for this common presentation. Issue 11 (18th November 2021) - Ree, Melissa J.; Richardson, Cele
Abstract: Insomnia is a chronic condition and major healthcare problem for Australians across the lifespan. Insomnia's high prevalence and disease burden render it an important target for treatment. Further, and importantly, there exist established bidirectional links between insomnia and a range of health conditions, with insomnia both contributing to risk, maintenance and relapse of comorbid conditions. Recent clinical research demonstrates that treating insomnia in its own right is important for resolution of insomnia and for optimising treatment outcomes for comorbid presenting problems. Due to its effectiveness and favourable side‐effect profile, Cognitive Behaviour Therapy‐Insomnia (CBT‐I) is the recommended first‐line treatment even when comorbid conditions are present. CBT‐I is a brief treatment often delivered in four to eight consultations. Individual, group and online CBT‐I have each demonstrated effectiveness. Outcomes for online CBT‐I are often stronger when individualised clinician support is provided. Specifically assessing for and treating insomnia in clinical practice may provide an opportunity to optimise treatment outcome in many patients.